Enhancing Customer Satisfaction: Exploring the Earliest Due Date Method for Production Scheduling at PT. X - Khusna, Arfiani Nur; Prabowo, Ferry Agung (Jurnal Nasional Pendidikan Teknik Informatika: JANAPATI, 2025)
Efficient production scheduling is essential for meeting customer demands on time and enhancing a company's operational efficiency. PT. X faces challenges in optimizing production schedules and meeting order deadlines efficiently. This study aims to evaluate the effectiveness of the earliest due date (EDD) method in production scheduling at PT. X. A quantitative approach was used, involving 100 production data samples from PT. X. The EDD method was applied to set the production order based on the earliest deadline of each order. Factors considered included order specifications, machine capabilities, and set deadlines. The EDD method improved the accuracy of production schedules, efficient use of resources, and customer satisfaction with on-time delivery. The results showed a 100% success rate for the EDD method in prioritizing orders based on the earliest deadlines, thereby improving production schedules and on-time delivery to customers. The study confirms the importance of the EDD method in enhancing production scheduling practices and achieving operational efficiency at PT. X. Future research should explore additional scheduling methods to further improve production processes and customer satisfaction.